2017
DOI: 10.1097/ico.0000000000001334
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Center and Flex-Center Methods of Corneal Endothelial Cell Analysis in the Presence of Guttae

Abstract: In corneas with guttae, both center and flex-center methods can reliably determine ECD. Although current practice recommends the center method when at least 100 cells can be counted, our study suggests that the center method can provide a reliable ECD value when there are ≥30 contiguous countable cells in a central cornea endothelial image. The flex-center method is recommended when <30 contiguous cells are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Huang and others reported that in corneas with guttae, the center method yields an accurate ECD value when there are ≥ 30 contiguous countable cells in an image. If the number of countable cells is less than 30, the flex-center method may be more suitable [ 15 ], and a minimum of 30 cells may be appropriate to obtain an accurate ECD value using the center method.…”
Section: Discussionmentioning
confidence: 99%
“…Huang and others reported that in corneas with guttae, the center method yields an accurate ECD value when there are ≥ 30 contiguous countable cells in an image. If the number of countable cells is less than 30, the flex-center method may be more suitable [ 15 ], and a minimum of 30 cells may be appropriate to obtain an accurate ECD value using the center method.…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve most reliable ECD values (single best is better than averaging), the graders were to grade on the best quality image of their own choice out of the three. ECD and CV values were evaluated using the Konan center method2527 in CellChek software. Any eye with very low ECD signifying pathologic endotheliopathy (ECD ≤ 800 cells/mm 2 ) were excluded from analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Our mean absolute difference between the two devices (93.3 cells/mm 2 , 3.45%) is significantly lower than the 5% cutoff defined by the Cornea Donor Study Group as an interobserver variance standard for good-quality analysis while using the same noncontact SM, the Konan machine. Huang et al 16,18 compared the fully automatic mode with the semiautomatic mode of the Konan SP-9900 device using the center and flex-center methods in normal and glaucomatous eyes. They found that automated analysis tended to overestimate ECD in both healthy control and diseased eyes, compared with semiautomated (manual) analysis.…”
Section: Discussionmentioning
confidence: 99%